Comparison of research case definitions for carpal tunnel syndrome - Descatha, Alexis (Institute of Occupational Health, 2011)
OBJECTIVE: The aim of our study was to assess agreement between different case definitions of carpal tunnel syndrome (CTS) for epidemiological studies. METHODS: We performed a literature search for papers suggesting case definitions for use in epidemiological studies of CTS. Using data elements based on symptom questionnaires, hand diagrams, physical examinations and nerve conduction studies collected from 1107 newly-hired workers, each subject in the study was classified according to each of the case definitions selected from the literature. We compared each case definition to every other case definition, using the Kappa statistic to measure pairwise agreement on whether each subject met the case definition. RESULTS: We found six unique papers in a twenty year period suggesting a case definition of CTS for use in population-based studies. We extracted seven case definitions. Definitions included different parameters: symptoms only, symptoms and physical examination, symptoms and either physical examination or median nerve conduction study, symptoms and nerve conduction study. When applied to our study population, the prevalence of CTS using different case definitions ranged from 2.5% to 11.0%. The percentage of misclassification was between 1 to 10%, with generally acceptable levels of agreement (Kappa values ranged from 0.30 to 0.85). CONCLUSION: Different case definitions resulted in widely varying prevalences of CTS. Agreement between case definitions was generally good, particularly between those that required very specific symptoms or the combination of symptoms and physical examination or nerve conduction. The agreement observed between different case definitions suggests that the results can be compared across different research studies of risk factors for CTS.